Physical Fitness Level Is Related to Attention and Concentration in Adolescents - Reigal, Rafael E.; Moral-Campillo, Luna; Mier, Rocío Juárez-Ruiz de; Morillo-Baro, Juan P.; Morales-Sánchez, Verónica; Pastrana, José L.; Hernández-Mendo, Antonio (Frontiers in Psychology, 2020)
The main goal of this study was to analyze existingrelationships among physical fitness, selective attention and concentration in a group of 210 teenagesr (43.81% male, 56.19% female) from the city of Malaga (Spain), aged between 11 and 15 years old (M = 13.27, SD = 1.80) that participated in the study. D2 attention test was used in order to analyze selective attention and concentration. Physical fitness was evaluated using the horizontal jump test, the Course Navette test and the 5 x 10 meter speed test. The analysis taken indicated a significant relationship among the physical fitness level, the attention and the concentration, as in the general sample as looking at gender. Linear regression tests performed showed that oxygen consumption is the best predictor of attentional parameters. Cluster analysis shows two groups characterized by a greater or lower physical fitness level. So, the the highest physical fitness level group scores better in the attention (e.g., boys: p< .001, d’ Cohen= 1.01, 95% CI [.57, 1.44]; girls: p< .01, d’ Cohen= .61, 95% CI [.24, .98]) and the concentration tests (e.g., boys: p< .001, d’ Cohen= .89, 95% CI [.46, 1.32]; girls: p< .01, d’ Cohen= .58, 95% CI [.21, .95]). Results indicate that physical fitness analysis can be used as a tool for observing differences in the attention and concentration level of the analyzed adolescents, suggesting that a physical performance improvement could be an adequate procedure to develop some cognitive functions during adolescence.